Massive Proteinuria and Autosomal Dominant Polycystic Kidney Disease: a Rare Coincidence (Iranian Journal of Kidney Diseases, 2012)
Autosomal dominant polycystic kidney disease (ADPKD) with nephrotic syndrome is a rare coincidence. Among 19 reported cases since 1972, focal glomerulosclerosis is the dominant reported pathology. Here, we report the 6th case of focal segmental glomerulosclerosis with ADPKD. A 29-year-old man with a history of APCDK presented with massive proteinuria. He had a history of concurrent leptospirosis and brucellosis, and trace proteinuria and mild hypertension had been diagnosed 4 years earlier. Urine study showed proteinuria (21 g/d) and hematuria. Kidney biopsy report was compatible with focal and segmental sclerosis. The patient received prednisolone and cyclosporine. After 4 months, proteinuria decreased to 600 mg/d. Patients with ADPKD who show massive proteinuria should undergo kidney biopsy. It is possible that different mutations in these patients could clarify the nature of this coincidence.